Islamic Legal Thought of a Modernist Islamic Organization: A Study of Family Law Fatwas According to Persatuan Islam - Marwadi Marwadi; Mughni Labib (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This article aims to analyze the family law thought of Persatuan Islam (Persis) and examine its relevance within the framework of contemporary Islamic legal thought. The study employs a library research method with a qualitative-descriptive approach. The primary sources consist of fatwas issued by the Persis Hisbah Council, which are analyzed using theoretical hermeneutics and discourse analysis. The discussion focuses on four major issues of family law: the legality of marrying a pregnant woman, the legal status of children born out of wedlock, family planning, and in vitro fertilization (IVF). The findings indicate that Persis is characterized by a legal orientation toward the purification of Islamic teachings, placing the Qur’an and Sunnah as the principal sources of legal reasoning (istinbāṭ). Regarding the issue of marrying a pregnant woman, Persis emphasizes the protection of lineage (nasab) by prohibiting marriage until childbirth has occurred. In the case of children born out of wedlock, Persis demonstrates a more progressive tendency by recognizing a lineage relationship with the biological father under certain conditions as a means of safeguarding children's rights. Concerning family planning, Persis permits temporary birth regulation for the welfare of the family while rejecting permanent birth limitation without legitimate sharīʿah-based reasons. With respect to in vitro fertilization, Persis allows IVF procedures involving sperm and ova from a legally married couple, while prohibiting third-party involvement due to its potential to compromise the purity of lineage. The analysis from the perspective of contemporary Islamic legal thought reveals that Persis selectively integrates a textual approach with considerations of maqāṣid al-sharīʿah. The family law thought of Persis thus represents a reformist-puritan orientation that seeks to respond to contemporary social and technological developments without departing from the fundamental principles of Islamic law.